Learning chemical concepts: a vision from some practical works and learning styles - Rodríguez-Cepeda, Rodrigo (Universidad Pedagógica y Tecnológica de Colombia, 2016)
It is very important that conceptual constructs achieved during college life can be applied within contexts of current social problems. However, difficulties of graduates for applying concepts are known, demonstrating insecurity of professional knowledge, isolation of environment reality, and out-of-date concepts. This happens, in spite of all efforts by professors and researchers at college, who have developed new ways of teaching, which are far distant from traditional memory-related approaches. In this context, this research focus on the construction of chemical concepts associated to chromatography within the context of food chemistry, identifying possible relations with the practical works and learning styles proposed by Honey and Mumford. The sample is seventh-semester students of a BA major in Chemistry, using a quasi-experimental design. The results indicate that the linking between the practical works and learning concepts benefits students with a pragmatic learning style.